2010
DOI: 10.1186/1471-2334-10-286
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of triggering receptor expressed on myeloid cells-1 and C-reactive protein for patients with lung infiltrates: an observational study

Abstract: BackgroundDifferential diagnosis of patients with lung infiltrates remains a challenge. Triggering receptor expressed on myeloid cells (TREM)-1 is a neutrophil and monocyte receptor up-regulated during infection. The aim of this study was to evaluate the diagnostic accuracy of TREM-1 and of C-reactive protein (CRP) from patients with lung infiltrates to discern community acquired lung infections.Methods68 patients admitted to a medical ward with acute respiratory illness were enrolled in the study. Neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
1
29
0
3
Order By: Relevance
“…A threshold procalcitonin value of 1.1 ng/mL achieved a sensitivity of 80% and a specificity of 82% in predicting in-patient mortality. A survival analysis using Kaplan-Meier curves and the log-rank test demonstrated that procalcitonin serum levels upon admission of Ͻ 1.1 ng/mL were associated with better survival (log- Congestive heart failure (26) Congestive heart failure (15) Chronic respiratory diseases (9) Chronic respiratory diseases (18) Chronic renal failure (6) Chronic renal failure (6) Psychiatric disease (10) Cognitive impairment (10) Cognitive impairment (41) Gastrostomy (4) Tracheostomy (3) Diagnoses (n) NHAP (58) Lung cancer (3) Streptococcus pneumoniae (8) Pulmonary embolism (4) Staphylococcus aureus (4) Congestive heart failure (7) Haemophilus influenzae (4) Bronchial asthma exacerbation (2) Pseudomonas aeruginosa (5) COPD exacerbation (10 rank test, P Ͻ .001) (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A threshold procalcitonin value of 1.1 ng/mL achieved a sensitivity of 80% and a specificity of 82% in predicting in-patient mortality. A survival analysis using Kaplan-Meier curves and the log-rank test demonstrated that procalcitonin serum levels upon admission of Ͻ 1.1 ng/mL were associated with better survival (log- Congestive heart failure (26) Congestive heart failure (15) Chronic respiratory diseases (9) Chronic respiratory diseases (18) Chronic renal failure (6) Chronic renal failure (6) Psychiatric disease (10) Cognitive impairment (10) Cognitive impairment (41) Gastrostomy (4) Tracheostomy (3) Diagnoses (n) NHAP (58) Lung cancer (3) Streptococcus pneumoniae (8) Pulmonary embolism (4) Staphylococcus aureus (4) Congestive heart failure (7) Haemophilus influenzae (4) Bronchial asthma exacerbation (2) Pseudomonas aeruginosa (5) COPD exacerbation (10 rank test, P Ͻ .001) (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that CPIS was useful in the diagnosis of CAP and VAP. 6,7 The assessment of CPIS is simple, calculating 6 variables (tracheal secretions, chest x-ray findings, temperature, WBC, P aO 2 /F IO 2 ratio, and microbiology). Tracheal secretions can be obtained via suction from subjects having difficulty secreting their sputum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations